ANALISIS REDAMAN KABEL PADA PERANGKAT ODC DAN ODP DALAM MODUL TRAINER JARINGAN FIBER TO THE HOME - Armenda, Annisa; Septima, Uzma; Yolanda, Amelia; Adila Asril , Aprinal; Adrian, Fachri (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Fiber to the Home (FTTH) is an optical fiber-based communication technology with high bandwidth capacity and low interference, making it the main choice for telecommunication network development. This study aims to analyze cable attenuation under various cable conditions in the FTTH trainer module. The research method involves designing an FTTH network using Optisystem and measuring cable attenuation under normal conditions, broken core, one splice, and two splices. The Optisystem simulation produced received power levels of -8.992 dBm (1310 nm) and -8.920 dBm (1550 nm), which correspond well with direct measurements on the trainer module. Measurements showed that normal cable attenuation was around 14 dB, cables with broken cores exceeded 50 dB, one splice added 0.2 dB, and two splices added 03–0.5 dB. The results indicate that splices in optical cables contribute to an increase in attenuation.